O papel de Apis Mellifera l. como polinizador da mamoneira (Ricinus Communis L.): avaliação da eficiência de polinização das abelhas e incremento de produtividade da cultura - Rizzardo, Rômulo Augusto Guedes (2007)
The research was carried out in the Núcleo de Produção Comunitária Santa Clara, idealized and administered by the Brasil Ecodiesel Indústria e Comércio de Biocombustíveis e óleos vegetais S. A., county of Canto do Buriti, state of Piauí, Brazil, and at the Universidade Federal do Ceará, located in Fortaleza, state of Ceará. Data were collected from April 2006 to January 2007 investigating castor bean (Ricinus communis L.) pollination, the role of biotic pollinating agents and the use of the honey bee Apis mellifera in its pollination. The study aimed to contribute in mitigating yield productivity losses in this crop. The following parameters were evaluated: floral biology, castor bean pollination requirements, A.mellifera pollination efficiency, foraging behavior of A.mellifera and Scaptotrigona bipunctata in castor bean inflorescences, and physiological evaluation of fruits and seeds produced. Results showed that both bee species harvested pollen and nectar throughout the day, but S. bipunctata prefers pollen much more than nectar. The castor bean plant accepts cross pollination, but it sets significantly (p<0.05) less fruits than self-pollination. The wind appeared as the main pollen vector in the plantation. Areas where honey bee colonies were introduced produced marginally (p = 0.08) more fruits than areas where no colony was made available. Similarly, they also led to significantly (p<0.05) more fruits per raceme (22.39) heavier seeds (0,54g) greater oil percentage (54.48%) and greater gross energy (9006.81kcal/kg) than those produced in areas without introduction of honey bee colonies (15.84, 0.47g, 49.94% e 8843.29kcal/kg, respectively), Physiological evaluation of seeds found no significant differences among treatments and produced an average 84% germination. It is concluded that the wind is the major pollinator of castor bean, and this species can be pollinated and set fruits both by means of cross and self-pollination, though showing better results under autogamy. The introduction of A. mellifera colonies in castor bean plantations contributes to increase crop productivity significantly, both increasing the number of fruits set per raceme and their oil content, probably because when collecting pollen honey bees increase the amount of self-pollen floating in the air around the panicles, favoring greater proportion of self-pollination.